MCPH1 maintains long‐term epigenetic silencing of ANGPT2 in chronic lymphocytic leukemia. (9th March 2015) - Kopparapu, Pradeep Kumar; Miranda, Caroline; Fogelstrand, Linda; Mishra, Kankadeb; Andersson, Per‐Ola; Kanduri, Chandrasekhar; Kanduri, Meena
<x xml:space="preserve">Abstract</x> The microcephalin gene (MCPH1) [also known as inhibitor of human telomerase reverse transcriptase (hTERT) expression] is a tumor suppressor gene that is functionally involved in the DNA damage response. Angiopoietin 2 (ANGPT2) is a crucial factor regulating tumor angiopoiesis. Deregulation of angiogenesis is one of the hallmarks of many cancers, including chronic lymphocytic leukemia (CLL). In CLL, ANGPT2 is a well‐studied potential prognostic marker. As MCPH1 overlaps with the ANGPT2 transcription unit on the same chromosome but in the opposite orientation, we wanted to study the functional role of MCPH1 in regulation of ANGPT2 in CLL. The mRNA expression levels of MCPH1 and ANGPT2, including the MCPH1 target gene hTERT, showed significant differences between two prognostic groups, i.e. IGHV‐mutated and IGHV‐unmutated (P = 0.007 for MCPH1, P = 0.0002 for ANGPT2, and P = 0.00001 for hTERT), in which the expression level of MCPH1 was inversely correlated with the expression levels of hTERT and ANGPT2. Downregulation of MCPH1 resulted in upregulation of ANGPT2, accompanied by loss of its promoter methylation. Using chromatin immunoprecipitation and coimmunoprecipitation assays, we found that MCPH1 binds to the ANGPT2 promoter and recruits DNA methyltransferases, thereby silencing ANGPT2. Thus, our data suggest a novel function for MCPH1 in regulating and maintaining ANGPT2 silencing in CLL through regulation of promoter DNA methylation.